2012
DOI: 10.1038/ejhg.2012.109
|View full text |Cite
|
Sign up to set email alerts
|

A variant in the carboxyl-terminus of connexin 40 alters GAP junctions and increases risk for tetralogy of Fallot

Abstract: GJA5 gene (MIM no. 121013), localized at 1q21.1, encodes for the cardiac gap junction protein connexin 40. In humans, copy number variants of chromosome 1q21.1 have been associated with variable phenotypes comprising congenital heart disease (CHD), including isolated TOF. In mice, the deletion of Gja5 can cause a variety of complex CHDs, in particular of the cardiac outflow tract, corresponding to TOF in many cases. In the present study, we screened for mutations in the GJA5 gene 178 unrelated probands with is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…This is based on several lines of evidence: (a) Gja5 heterozygous and homozygous knock-out mice show various cardiac malformations [Gu et al, 2003]; (b) germline and somatic mutations in GJA5 predispose to atrial fibrillation [Gollob et al, 2006;Yang et al, 2010;Wirka et al, 2011]; (c) small (100-200 kb) rare duplications encompassing only the GJA5 gene are enriched in patients with non-syndromic TOF [Soemedi et al, 2012]; (d) and lastly, a missense variant (p.Pro265Ser) at the carboxylterminus of GJA5 was detected in 2/178 patients with non-syndromic TOF. This variant was not observed in 1,568 ethnically-matched controls [Guida et al, 2012]. The hypertrabeculated myocardium observed in patient IV-1 has not been reported previously in patients with 1q21.1 microduplications.…”
Section: Discussionsupporting
confidence: 42%
“…This is based on several lines of evidence: (a) Gja5 heterozygous and homozygous knock-out mice show various cardiac malformations [Gu et al, 2003]; (b) germline and somatic mutations in GJA5 predispose to atrial fibrillation [Gollob et al, 2006;Yang et al, 2010;Wirka et al, 2011]; (c) small (100-200 kb) rare duplications encompassing only the GJA5 gene are enriched in patients with non-syndromic TOF [Soemedi et al, 2012]; (d) and lastly, a missense variant (p.Pro265Ser) at the carboxylterminus of GJA5 was detected in 2/178 patients with non-syndromic TOF. This variant was not observed in 1,568 ethnically-matched controls [Guida et al, 2012]. The hypertrabeculated myocardium observed in patient IV-1 has not been reported previously in patients with 1q21.1 microduplications.…”
Section: Discussionsupporting
confidence: 42%
“…Novel genes have been constantly reported in association with CHD. Since the design of this capture panel, mutations in GATA5, BVES , and GJA5 were shown to cause sporadic or familial TOF [Guida et al, ; Wei et al, ; Wu et al, ], MEF2C mutations were identified in patients with outflow tract defects [Kodo et al, ], NPHP4 and DICER1 variants were described in association with TGA [Foulkes et al, ; French et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting study published this year (Guida et al, 2013) characterized over 150 patients with non-syndromic Fallot and found in 1% of their patients a heterozygous nucleotide change in the Cx40 gene leading to altered amino acid sequence. This Pro265Ser variant was not seen in healthy volunteers [amino acid 265 is the binding region for src (sarcoma Rous kinase)].…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%